2016
DOI: 10.5194/acp-16-561-2016
|View full text |Cite
|
Sign up to set email alerts
|

Possible influence of atmospheric circulations on winter haze pollution in the Beijing–Tianjin–Hebei region, northern China

Abstract: Abstract. Using the daily records derived from the synoptic weather stations and the NCEP/NCAR and ERA-Interim reanalysis data, the variability of the winter haze pollution (indicated by the mean visibility and number of hazy days) in the Beijing-Tianjin-Hebei (BTH) region during the period 1981 to 2015 and its relationship with the atmospheric circulations at middle-high latitude were analyzed in this study. The winter haze pollution in BTH had distinct inter-annual and inter-decadal variabilities without a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 34 publications
0
60
0
1
Order By: Relevance
“…Aerosol concentrations are also strongly modulated by monsoon circulation through surface winds, rain scavenging, and stratification stability (Chen & Wang, ; Jeong & Park, ; Jia et al, ; Liu, Sheng, et al, ; Zhang et al, ). In summer, haze‐fog events are related to the monsoon‐induced changes in air flow transport and moisture convergence over eastern China (Liu, Sheng, et al, ; Wu et al, ).…”
Section: Impact Of Aerosols On Regional Climatementioning
confidence: 99%
“…Aerosol concentrations are also strongly modulated by monsoon circulation through surface winds, rain scavenging, and stratification stability (Chen & Wang, ; Jeong & Park, ; Jia et al, ; Liu, Sheng, et al, ; Zhang et al, ). In summer, haze‐fog events are related to the monsoon‐induced changes in air flow transport and moisture convergence over eastern China (Liu, Sheng, et al, ; Wu et al, ).…”
Section: Impact Of Aerosols On Regional Climatementioning
confidence: 99%
“…In particular, weather conditions play an essential role in controlling the daily variability of air pollutant concentrations 5,3234 . Previous studies have suggested that there is a close relationship between the occurrence of winter haze pollution in the Beijing-Tianjin-Hebei region and atmospheric circulation at middle to high latitudes over a long-term perspective 35–37 . In addition, on interannual time scales, the air pollution across central and eastern China or even South Asia in the winter and summer is closely related to the East Asian winter and summer monsoons, respectively 3845 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, meteorological conditions control the occurrence of haze pollution [3,[7][8][9][10][11][12][13][14][15][16][17][18][19]. In China, most studies are focused on the Jingjinji area (Beijing), the Yangtza river delta (Shanghai), and the Pearl River delta (Guangzhou, Zhujiang).…”
Section: Introductionmentioning
confidence: 99%